KONFLIK DAN IRONI YANG DIALAMI TOKOH YUSUF DALAM KISAH INJIL MATIUS 1:18 – 25 - Walewangko, Stief Aristo (PBSI STKIP Persada Khatulistiwa Sintang, 2021)
The purpose of this research is to describe the conflict and irony that Yusuf faces in the Gospel of Matthew 1:18–25. This study utilizes a qualitative descriptive method that includes data collection techniques such as literature reviews and data analysis procedures such as reading, identifying, recording, connecting, and interpreting data. The source of this research is the story of Matthew 1:18 – 25. The result of this research shows that the conflict in Matthew 1:18 – 25 is an internal conflict which is the struggle of Joseph, facing the truth that his fiancée, Maria, were pregnant before they live as a husband and wife. Furthermore, there are three kinds of irony in Matthew 1:18 – 25, such as: verbal irony, dramatic irony and situational irony. Verbal irony shows in two ways: (1) Joseph takes Maria as his wife, but does not have sexual intercourse with her; (2) Joseph, a just man and unwilling to put Maria into shame, resolved to divorce her quietly. Dramatic irony describes when Joseph finds that Maria is pregnant before they’re getting married, and plans to divorce her, whereas she is not having child with another guy. Situational Irony takes place when Joseph resolves to divorce Maria, but in the end, he takes her as his wife precisely.